Commodity Taxation and Parallel Imports - Pascalis Raimondos-Møller; Nicolas Schmitt (Copenhagen Business School (CBS), Department of Economics, 2007)
We examine the interaction between commodity taxes and parallel imports in a simple two-country model with imperfect competition. While governments determine non-cooperatively their commodity tax rate, the volume of parallel imports is determined endogenously by the retailing sector. We compare the positive and normative implications of having commodity taxes based on destination or origin principle. Origin taxes are shown to have very attractive properties: they lead to lower levels of optimal taxes, they converge as parallel imports increase (while destination taxes diverge), and they lead to higher welfare levels
hdl:10398/7538
Keywords: G10; 330